FRI0354 Cardiopulmonary Involvement in Takayasu Arteritis. (15th July 2016) - Brennan, D.; Warrington, K.J.; Schmidt, J.; Crowson, C.; Koster, M.J.
Abstract : Background: Takayasu arteritis (TAK) is an inflammatory large-vessel vasculitis of unknown etiology affecting the proximal aorta and its primary branches. Heart disease is a major cause of death in patients with TAK but studies evaluating coronary/pulmonary artery involvement and myocardial dysfunction in this population have been limited. Objectives: To evaluate cardiopulmonary (CP) involvement in patients with TAK and assess the impact on disease outcomes. Methods: A retrospective cohort of patients with newly diagnosed TAK from 1984 to 2009 was assembled. All patients included met 1990 American College of Rheumatology classification criteria for TAK. Demographics, baseline disease characteristics, relapse events, surgeries and mortality were abstracted from direct medical record review. Angiograms (invasive and non-invasive), echocardiograms, nuclear medicine scans, and electrocardiograms (ECG) were reviewed for evidence of CP involvement. For the purpose of this study, CP abnormalities were defined as coronary or pulmonary artery vasculitis, left ventricular (LV) dysfunction, left atrial (LA) enlargement, moderate-severe valvular disease, pulmonary arterial hypertension (PAH), regional wall hypokinesis/akinesis, LV hypertrophy or persistent ECG axis deviation. Cox models with time-dependent covariates were used to assess the association between CP involvement and outcomes. Results: A total of 117 patients with TAK were identified. The mean (±SD) age at diagnosis was 31.8 (±10.5) years. Fifty-four (46%) patients had at least one objective CP abnormality observed during the course of follow-up. No difference in age, sex, inflammatory markers or Hata classification were seen between those with and those without CP involvement. Baseline characteristics and symptoms were similar, except shortness of breath, which was more frequently observed at TAK diagnosis in patients with CP involvement compared to those without (54% vs 33%, respectively; p=0.035). PAH was identified in 8, pulmonary arteritis in 9, coronary arteritis in 3, aortic valve insufficiency in 10 (6 moderate, 4 severe), LV systolic heart failure in 5, LV enlargement in 19, and LA atrial enlargement in 21 patients. Seventy-nine patients had at least 1 year of follow-up [median (IQR): 5.5 (2.9–10.1) years]. Of these 79 patients, 46 had at least one vascular or valvular surgery during the follow-up period. Composite CP involvement was not associated with risk of first surgery [Hazard ratio (95% CI): 1.40 (0.75–2.59); p=0.29]. However, PAH on echocardiogram was significantly associated with risk of first surgery [HR (95% CI): 14.2 (2.1–96.9); p=0.007]. During follow-up 6 patients died. CP involvement was not significantly associated with mortality [HR (95% CI): 1.81 (0.30–10.98); p=0.52]. Conclusions: Cardiopulmonary abnormalities in TAK are common. In this population, the presence of PAH predicted a 14-fold increased risk for vascular or valvular surgery. In this cohort, the presence of CP involvement did not increase mortality. Disclosure of Interest: None declared